Vegetation analysis and population of tarsier (Tarsius spectrumgurskyae) at Batuputih Nature Tourism Park, North Sulawesi, Indonesia - ARRIJANI; MUHAMMAD RIZKI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Arrijani, Rizki M. 2019. Vegetation analysis and population of tarsier (Tarsius spectrumgurskyae) at Batuputih Nature Tourism Park, North Sulawesi, Indonesia. Biodiversitas 20: 530-537. Tangkasi or Tarsius (Tarsius spectrumgurskyae) is a world’s smallest primate, which categorized as an endemic and protected species inhabited Sulawesi Island. Batuputih Nature Tourism Park (Batuputih NTP) at Tangkoko Batuangus Nature Reserve, Bitung City, North Sulawesi, Indonesia is one of the habitats of the primate. The research aimed to characterize the habitats of Tarsius that include physical and vegetation characteristics and to figuring out the nest distribution and estimation of the population of this species. The vegetation data were sampled using a quadrat sampling technique around Tarsius nests. The Tarsius population was estimated along a 2 km transect line with the distance 50 m to the left and right across the line (the total width 100 m (0.1 km). Meanwhile, to calculate population abundance (Overall estimate of population size/abundance) can be obtained by multiplying population densities with the total area of ??all observations. The result revealed that the vegetation types of Tarsius habitats were dominated by tree species which associated with Liana from the family Araliaceae, among them include Spathodea campanulata, Ailanthus integrifolia, Kleinhovia hospital, Alstonia scholaris, Garuga floribunda, Arenga pinnata, and two sleeping trees without accosiated from the species of Ficus tinctoria and Ficus variegata. Tarsius life in groups with 2-8 individuals per group. The estimation of population density was found that there were 270 individuals/km or 2.7 individuals/ha and their total abundance around 1660 individuals of Tarsius lived in Batuputih NTP.